An audit of drugs return from medical wards to Inpatient Pharmacy Department, HUSM / Fatin Azzyati Pakururazi and Nurul Nurhayatul Syima Mohamad Ariffin - Pakururazi, Fatin Azzyati; Mohamad Ariffin, Nurul Nurhayatul Syima (2010)
Underutilize medicines are regarded as a common problem in Hospital Universiti Sains Malaysia,(HUSM).All wards are advised to return unused medicines to Inpatient Pharmacy for recording, reusing and eradication purpose. Inpatient Pharmacy in HUSM supplies medications to patients in the wards via unit dose system. The medication are supplied 3 days per week which are on Sunday, Tuesday and Thursday. Suprisingly, there were abundant of drugs returned to Inpatient Pharmacy, especially from medical wards. This study was conducted in order to find the factors that contribute to drug return from medical wards to Inpatient Pharmacy Department, HUSM. This study was also done to suggest suitable solution to those problems. Prospective observational study was used as a method in conducting the research. We have chosen drug return from medical wards (Ward 7 Utara and 7 Selatan) as our source of data. The data was collected 3 times weekly (Sunday, Tuesday and Thursday) for 11 weeks, from 13 October 2009 till 27 December 2009 . In questionnaire session, 35 respondents were choose randomly including physician, inpatient pharmacy’s staff and ward’s staff in order to help us identify the factors that contribute to the drug return to Inpatient Pharmacy. A “Drug Return Form” was created by that and the form was used to record the data. Then, the obtained data was analyzed by using SPSS 17.0 and Microsoft Excel 2007.Based on the research conducted, we know that, discharged/transfer patient is the highest factor that contribute to drug return from medical wards(7 Utara and 7 Selatan) to Inpatient Pharmacy with 2863 factors and the lowest is expired drug with 0 factor. We also found that 25109.75 drug were given by Inpatient Pharmacy to medical wards from 13 October 2009 till 27 December 2009 and 11648.75 were returned back. That means,47% of drug are returned back and it is quite a number. Meanwhile, from that, 12939.5 of drug return are in tablet form and 4474 are in injection form .As a conclusion, we suggest that a programme should be instill to educate ward’s staff, physician, and pharmacy staff itself regarding Unit Dose practiced Pharmacy Department, HUSM.